Kanuns in Albania and Bloodfeud According to Kanun of Lekë Dukagjini - Shkurtaj, Gelanda (European Journal of Sustainable Development, 2020)
In societies where it has been known and applied, bloodfeud is described as a possibly outdated and uncivilized mechanism, but often effective to limit violence. Indeed, both in form and substance the phenomenon itself is hard to be perceived and understood by the modern citizen of every country of the world, including Albania, where it is still active in some regions in respect of “Kanun”. In fact, the Albanian term ’Kanun’ describes the body of traditional norms/standards and rules governing society in the field of criminal, civil and procedural laws. Its application or merely its existence in moral and legal standards makes a society safer, certainly referring to a society where the power of central authority, namely of the state, either did not exist or lacked. The greatest anthropological dilemma is just there, why does Kanun work in a modern state? In societies where blood feud has been present as a regulatory element of social conflicts it is accepted that its abolition or decline occurred only when another subject (the state), took over to intervene in these conflicting relationships, and to provide the resolution and regulation of social and economic relations through enforcement of rule of law, or the public order. And the question arises by itself: why the Albanian state did not take over the blood feud solution by use of public order? The Kanun does not recognize the state or the state does not recognize the Kanun? Why? It is not easy to get into such historic and social dilemmas, but a modest effort should be made. The answer to this fact should be found by the history of Albania. As a questioning remark, the reason for the long life of Kanun, rather called as self-regulatory law of the society, is due to the historic absence of a state on the side and interests of its citizens. Keywords: Kanun, Legal and Religious norms, Mechanic solidarity, Bloodfeud, Survival, State, Coexistence